Investigation on taste characteristics and sensory perception of soft-boiled chicken during oral processing based on electronic tongue and electronic nose - Na Xu; Xianming Zeng; Peng Wang; Xing Chen; Xinglian Xu; Minyi Han (Food Science and Human Wellness)
The sensory perception of food is a dynamic process, which is closely related to the release of flavor substances during oral processing. It's not only affected by the food material, but also subjected to the individual oral environment. To explore the oral processing characteristics of soft-boiled chicken, the sensory properties, texture, particle size, viscosity, characteristic values of electronic nose and tongue of different chicken samples were investigated. The correlation analysis showed that the physical characteristics especially the cohesiveness, springiness, resilience of the sample determined oral processing behavior. The addition of chicken skin played a role in lubrication during oral processing. The particle size of the bolus was heightened at the early stage, and the fluidity was enhanced in the end, which reduced the chewing time to the swallowing point and raised the aromatic compounds signal of electronic nose. But the effect of chicken skin on chicken thigh with relatively high fat content, was opposite in electronic nose, which had a certain masking effect on the perception of umami and sweet taste. In conclusion, fat played a critical role in chicken oral processing and chicken thigh had obvious advantages in comprehensive evaluation of soft-boiled chicken, which was more popular among people.